2012
DOI: 10.1097/qad.0b013e328353f363
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malnutrition and social determinants on survival of HIV-infected adults starting antiretroviral therapy in resource-limited settings

Abstract: Malnutrition and anaemia are strong and independent prognostic factors at the time of starting ART. Nutritional cares are essential for the clinical success of HIV programs started in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 25 publications
(25 reference statements)
3
37
0
2
Order By: Relevance
“…According to study performed by Grzeszczuk et al, no association was found between HCV seropositive and survival, and this result was in agreement with our findings [27]. Based on conducted studies in HIV patients, low CD4+ T-cell count at the time of tuberculosis treatment initiation was associated with early mortality and increased risk of death [28][29][30][31]. Also another study showed that history of tuberculosis and not using antiretroviral drugs was significantly associated with higher mortality in HIV patients [32].…”
Section: Discussionsupporting
confidence: 82%
“…According to study performed by Grzeszczuk et al, no association was found between HCV seropositive and survival, and this result was in agreement with our findings [27]. Based on conducted studies in HIV patients, low CD4+ T-cell count at the time of tuberculosis treatment initiation was associated with early mortality and increased risk of death [28][29][30][31]. Also another study showed that history of tuberculosis and not using antiretroviral drugs was significantly associated with higher mortality in HIV patients [32].…”
Section: Discussionsupporting
confidence: 82%
“…While this is good news, there are certain factors associated with poor outcomes. For example, in subSaharan Africa, malnutrition in the form of low body mass index (BMI) is common at ART initiation ranging from 10% to 33% [12][13][14][15] and this is associated with poor treatment outcomes and increased mortality [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…A major contributing factor is that over 800 million people remain chronically undernourished globally, and the HIV epidemic largely overlaps with populations already experiencing low diet quality and quantity. Malnutrition, and more specific under nutrition, is generally associated with increased mortality among HIV infected individuals initiating Antiretroviral Therapy (ART) [1,2]. …”
mentioning
confidence: 99%